2021
DOI: 10.1038/s41586-021-03923-3
|View full text |Cite|
|
Sign up to set email alerts
|

In situ formation of ZnOx species for efficient propane dehydrogenation

Abstract: Propane dehydrogenation (PDH) to propene is an important alternative to oil-based cracking processes, to produce this industrially important platform chemical1,2. The commercial PDH technologies utilizing Cr-containing (refs. 3,4) or Pt-containing (refs. 5–8) catalysts suffer from the toxicity of Cr(vi) compounds or the need to use ecologically harmful chlorine for catalyst regeneration9. Here, we introduce a method for preparation of environmentally compatible supported catalysts based on commercial ZnO. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
184
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(200 citation statements)
references
References 44 publications
1
184
0
Order By: Relevance
“…Besides zeolite-supported Pt catalysts, some cost-effective zeolite-supported non-noble monometal catalysts (e.g., Ga, 57,62,98,[106][107][108][109][110] Sn, 63 and Zn 102,111 ) and non-noble monometal oxide catalysts (such as ZnO, 45,56,61,65,66 CrO x , 60 CoO, 46,58 and VO x 64,112,113 ) were also extensively studied for PDH reactions. Supported CrO x catalysts have been used for a long time in industrial PDH plants since 1964, one of which is the FBD-4 process that uses Al 2 O 3 as a support.…”
Section: Zeolite-supported Non-noble Monometal Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides zeolite-supported Pt catalysts, some cost-effective zeolite-supported non-noble monometal catalysts (e.g., Ga, 57,62,98,[106][107][108][109][110] Sn, 63 and Zn 102,111 ) and non-noble monometal oxide catalysts (such as ZnO, 45,56,61,65,66 CrO x , 60 CoO, 46,58 and VO x 64,112,113 ) were also extensively studied for PDH reactions. Supported CrO x catalysts have been used for a long time in industrial PDH plants since 1964, one of which is the FBD-4 process that uses Al 2 O 3 as a support.…”
Section: Zeolite-supported Non-noble Monometal Catalystsmentioning
confidence: 99%
“…The DFT calculation demonstrated that the CoO clusters could promote pro- pylene desorption and prevent an over-dehydrogenation reaction, affording excellent catalytic performance in PDH reactions, while the isolated Co 2+ sites in the zeolite frameworks possessed a higher dehydrogenation barrier than the CoO clusters due to the spatial restriction of the closed framework site, showing rather poor activity for the dehydrogenation of propylene. Besides zeolite-supported Co catalysts, other zeolite-supported non-noble monometal catalysts, such as ZnO/S-1, 45 Zn/Beta, 65 ZnO/Y, 66 Zn/HZSM-5, 61 Zn/S-1, 56 Ga/H-ZSM-5, 110 V/FAU, 113 Ga/ SiBEA, 62 Ga/ZSM-5 59 and GaN/NaZSM-5 57 have also been developed and exhibited high performances in PDH reactions.…”
Section: Zeolite-supported Non-noble Monometal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Propane dehydrogenation (PDH) is currently an instance of potential yet challenging chemistry, meeting the increasing cosmopolitan demand for propylene. [4][5][6] On reviewing the development of Ptbased catalysts, [7][8][9] introducing a second metal (M) to form Pt-M alloys, such as Pt-Sn, [10][11][12][13] Pt-Zn, [14][15][16] Pt-Fe, 17 Pt-Cu, 18,19 Pt-Ga 20 and Pt-In, 21 is a practical approach to improving the activity and selectivity, accompanied by reducing the Pt usage. Among them, the Pt-Cu alloy catalyst as has been extensively investigated as an effective candidate for PDH.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They are produced in industry mainly from the catalytic cracking and reforming of naphtha, 1,[4][5][6] using petroleum as the raw material. In recent years, various non-oil-based processes with coal-derived syngas (CO/CO 2 /H 2 ), [7][8][9][10][11][12][13] synthesized methanol 14,15 and light alkanes (CH 4 , C 2 H 6 and C 3 H 8 ) [16][17][18][19][20][21] have been developed for producing olefins and aromatics, meeting their increasing market demand. In comparison to the reactions with methane as a feedstock, such as non-oxidative methane dehydroaromatization (MDA) 18,22,23 and oxidative coupling of methane (OCM), 16,17 conversion of ethane and propane into olefins or/and aromatics that can take place at mild reaction temperatures (400-650 °C) has attracted more attention and interest, [19][20][21] especially considering that a large portion of these low-cost hydrocarbons existed in shale gas.…”
Section: Introductionmentioning
confidence: 99%